Farm Machinery and Processes Management in Sustainable Agriculture, IX International Scientific Symposium 2017
DOI: 10.24326/fmpmsa.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent Polarity on the Efficiency of Ultrasound-Assisted Extraction of Polyphenols From Apple Pomace

Abstract: In this paper influence of solvent polarity on the efficiency of ultrasound-assisted extraction of polyphenols from apple pomace was studied. In the experiment, three solvents were used: water, 60% ethanol and 96% ethanol. The extraction process was aided by ultrasonic waves at intensity of 60 W. Efficiency of extraction was determined by measuring total phenolic content, antioxidant activity, energy consumption and unit energy consumption. It has been shown that a 60% solution of ethanol is the most effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
(16 reference statements)
1
9
0
Order By: Relevance
“…The influence of the ultrasonic treatment parameters on unit energy consumption during the extraction of bioactive substances is relatively poorly described in the literature. Kobus et al [59] showed that an important factor determining the energy consumption during ultrasonic extraction is the appropriate selection of the solvent. Energy efficiency analysis has shown that using 60% ethanol allows obtaining the lowest unit energy input.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the ultrasonic treatment parameters on unit energy consumption during the extraction of bioactive substances is relatively poorly described in the literature. Kobus et al [59] showed that an important factor determining the energy consumption during ultrasonic extraction is the appropriate selection of the solvent. Energy efficiency analysis has shown that using 60% ethanol allows obtaining the lowest unit energy input.…”
Section: Discussionmentioning
confidence: 99%
“…High-intensity and high-power active ultrasound techniques have the capacity to interact with raw material (matter) and can modify the course of physical or chemical processes. Ultrasound can be used to increase pressing efficacy [11], to support the process of extracting different components (herb extracts, polyphenols, aromatic compounds, polysaccharides) [12][13][14], and to improve the quality of obtained products [15]. Some authors have studied the potential of ultrasound for use in the preservation of fruit juice [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its different molecular structure, ethanol is more effective at eluting compounds like chlorogenic acid and flavonoids [ 16 ]. Water is a more effective solvent due to its higher polarity coefficient [ 18 ]. As a result, combining water and ethanol yields a higher polyphenol extraction efficiency than using these solvents separately.…”
Section: Resultsmentioning
confidence: 99%
“…The first 20 min could be the washing stage during the extraction process, which means that the extraction process could recover up to 90% of the extract during this period. This is also the stage where the dissolution of the soluble components on the surface of the plant matrix takes place [ 17 , 18 ]. The second stage should follow which is called slow extraction which can take up to 60 min; however, it should be noted that the purpose of the process is to limit the sonication duration and also to reduce the energy cost of the process.…”
Section: Resultsmentioning
confidence: 99%